PERBANDINGAN JOB CHARACTERISTIC PADA ORGANISASI DI LINGKUNGAN PEMERINTAH DAERAH, BUMN/BUMD, DAN TNI/POLRI - Ely Sufianti (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
Each organization has its own characteristics, depending on its goals. This research tries to find out how the job characteristics of local government, local state owned enterprises, and military organizations differ based on their services. Data are collected through STIA LAN Bandung students who work for those organizations. The indicators for job characteristic are job variety, autonomy, feedback, task identity, interaction with others, and friendship. The result shows that both friendship and feedback within local government organizations are significantly different from those within local state owned enterprises whereas autonomy within local state owned enterprises is significantly different from those within military organizations.